Caminhos cotidianos de Txeramõi e Txedjaryi: interlocuções sobre saberes e fazeres guarani - Neves, Amabile Teresa Modenez (2018)
This work aims to understand which are the everyday practices of txeramõi (old men) and txedjaryi (old women) and how they contribute to the circulation and maintenance of Guarani know-doings on transmission of nhandereko (way of being Guarani), considering their intergerational, social and cultural dynamics. This study has its methodological basis on ethnography, with interviews and fieldwork realized among Guarani Mbya villages in Aracurz-ES. It was realized that the everyday practices of elder men and women in familiar and community context don’t encompass only spiritual activities, but also educational and from-the-word activities, in a way that the roles taken travel among grandparents, advisers, religious leaders, prayers, healers and educators. Beyond this, the intention of maintenance and circulation of nhandereko (way of being Guarani) is the same in all everyday activities that were watched. This experience purposes to think about the relevance of the being/person notion to theoretical framework and to the intervention practices in Occupational Therapy, Gerontology and its areas and sociocultural contexts, once that, being a conception that precedes the human doing, it was noticed that it is related to the development of approaching ways and dialogues to differentiated realities and problems, especially in a socio-cultural way. Thereby, there is a collaboration to intercultural dialogue and to the enlargement of knowings and debates about the ways of living in old age in a context of traditional people and communities, especially Guarani Mbya.